2018
DOI: 10.1002/iid3.235
|View full text |Cite
|
Sign up to set email alerts
|

A 21.6 kDa tegumental protein of Clonorchis sinensis induces a Th1/Th2 mixed immune response in mice

Abstract: Introduction Clonorchis sinensis is a major parasite affecting the Korea population. Despite the high infection rate and pathogenicity, very few studies have been conducted to investigate the immune responses against the proteins of C. sinensis.MethodsIn this study, in vitro immune response induced by a recombinant 21.6 kDa tegumental protein derived from C. sinensis (rCsTegu21.6) was confirmed in murine dendritic cells and T cells. For the in vivo analysis, each mouse was immunized three times. Total serum Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This complexity results from the fact that the parasite produces different types of compounds involved in its pathogenicity. Generally, during the life cycle of its definitive host, there are massive compounds of the parasite included excretory-secretory products (ESPs), tegumental proteins ( Chung et al, 2018 ), cyst wall-derived proteins ( Wang et al, 2012 ), egg-derived proteins ( Chen et al, 2017 ), and metabolism-related enzymes among others ( Shi et al, 2020 ). Furthermore, it seems that some compounds excreted by the parasite appear to depend on its stages of development, which implies that the juvenile in the early stages of infection may secrete specific compounds that are different from those excreted in the other stages of infection ( Table 1 ; Figure 2 ) ( Wang et al, 2012 ; Bian et al, 2014 ; Mao et al, 2015 ; Xu et al, 2015 ; Chen et al, 2017 ).…”
Section: Mechanism Of Immunity To Clonorchis Sinensismentioning
confidence: 99%
See 3 more Smart Citations
“…This complexity results from the fact that the parasite produces different types of compounds involved in its pathogenicity. Generally, during the life cycle of its definitive host, there are massive compounds of the parasite included excretory-secretory products (ESPs), tegumental proteins ( Chung et al, 2018 ), cyst wall-derived proteins ( Wang et al, 2012 ), egg-derived proteins ( Chen et al, 2017 ), and metabolism-related enzymes among others ( Shi et al, 2020 ). Furthermore, it seems that some compounds excreted by the parasite appear to depend on its stages of development, which implies that the juvenile in the early stages of infection may secrete specific compounds that are different from those excreted in the other stages of infection ( Table 1 ; Figure 2 ) ( Wang et al, 2012 ; Bian et al, 2014 ; Mao et al, 2015 ; Xu et al, 2015 ; Chen et al, 2017 ).…”
Section: Mechanism Of Immunity To Clonorchis Sinensismentioning
confidence: 99%
“…Furthermore, it seems that some compounds excreted by the parasite appear to depend on its stages of development, which implies that the juvenile in the early stages of infection may secrete specific compounds that are different from those excreted in the other stages of infection ( Table 1 ; Figure 2 ) ( Wang et al, 2012 ; Bian et al, 2014 ; Mao et al, 2015 ; Xu et al, 2015 ; Chen et al, 2017 ). Although the compounds of C. sinensis proteins are complex, the available data showed that recombinant proteins derived from ESPs, tegumental proteins, egg-derived proteins, or proteins extracted directly from ESPs generally and preferentially target a specific immune cell type including innate immune cells such as macrophages, dendritic cells, and/or adaptive immune cells such as T lymphocytes ( Table 1 ) ( Habich et al, 2005 ; Xu et al, 2015 ; Kim et al, 2017b ; Chung et al, 2018 ; Zhao et al, 2018 ).…”
Section: Mechanism Of Immunity To Clonorchis Sinensismentioning
confidence: 99%
See 2 more Smart Citations
“…, activating phagocytes, NK cells, and others to directly kill Clonorchis sinensis . Chung et al [ 70 ] confirmed that the Clonorchis sinensis coat protein rCsTegu21.6 stimulated T cell-specific antibody production and cytokine production of IL-2, IL-4, and IFN-γ in murine dendritic cells and T cell secretion. Th2 mainly produce IL-4, IL-5, IL-6, IL-10, IL-13, and other cytokines to promote the maturation of B cells, produce antibodies, and regulate humoral immunity.…”
Section: Clonorchis Sinensis and Igg4mentioning
confidence: 99%